The use of small emitter flow rate in drip irrigation favored methane uptake in arid potato fields - Jianyu Zhao; Chaobiao Meng; Kaijing Yang; Clinton C. Shock; Ning Wang; Fengxin Wang (Agricultural Water Management, 2024)
Drip irrigation has been widely used in agriculture, while the mechanism underlying the effect of drip irrigation system design and management on soil methane (CH4) uptake have not been fully studied. A two-year experiment was conducted to explore the effects of different emitter flow rates of drip irrigation (1.3, 2.0, and 3.0 L/h) on CH4 uptake in potato fields in an arid region of Northwest China. Results showed that compared to emitter flow rates of 2.0 and 3.0 L/h, the 1.3 L/h flow rate significantly increased the cumulative CH4 uptake by 6.3–16.2%, mainly due to the increase in the abundance of the pmoA gene by 15.2–49.5%, and by the decrease of water-filled pore space (WFPS), increasing the effective CH4 diffusion coefficient (Dp) and soil oxygen concentration in the topsoil. A hump-shaped relationship was found between WFPS and CH4 uptake flux, and the optimum WFPS for CH4 uptake was about 44.8%. The treatment with an emitter flow rate of 1.3 L/h exhibited the highest frequency (28.6%) of favorable WFPS for CH4 uptake, compared to the 2.0 and 3.0 L/h treatments. In addition, significant negative quadratic relationships were observed between both Dp and soil oxygen with CH4 uptake, and optimal values were 0.02 cm2 s−1 and 18.7%, respectively. There was no significant difference in CH4 uptake between 2.0 and 3.0 L/h treatments in 2021 and 2022, due to high WFPS and low oxygen concentrations in both treatments. Multiple linear regressions indicated that soil oxygen concentration became a major limiting factor under emitter flow rates of 2.0 and 3.0 L/h. This study provides insights into mechanisms of soil CH4 uptake in drip-irrigated farmland, which gives guidance on developing irrigation strategies for sustainable production and CH4 mitigation in irrigated arid land.